The global city : New York, London, Tokyo - Sassen, Saskia; Princeton University Press (Princeton, N.J. : Princeton University Press, 2001)
This classic work chronicles how New York, London, and Tokyo became command centers for the global economy and in the process underwent a series of massive and parallel changes. What distinguishes Sassen's theoretical framework is the emphasis on the formation of cross-border dynamics through which these cities and the growing number of other global cities begin to form strategic transnational networks. All the core data in this new edition have been updated, while the preface and epilogue discuss the relevant trends in globalization since the book originally came out in 1991.
-- One Overview -- PART ONE: THE GEOGRAPHY AND COMPOSITION OF GLOBALIZATION -- Two Dispersal and New Forms of Centralization-- Mobility and Agglomeration -- Capital Mobility and Labor Market Formation -- Conclusion -- Three New Patterns in Foreign Direct Investmen t-- Major Patterns-- International Transactions in Services-- Conclusion -- Four Internationalization and Expansion of the Financial Industry -- Conditions and Components of Growth -- The Global Capital Market Today -- Financial Crises -- Conclusion -- PART TWO: THE ECONOMIC ORDER OF THE GLOBAL CITY -- Five The Producer Services -- The Category Services -- The Spatial Organization of Finance -- New Forms of Centrality -- Conclusion -- Six Global Cities: Postindustrial Production Sites -- Location of Producer Services: Nation, Region, and City -- New Elements in the Urban Hierarchy -- Conclusion -- Seven Elements of a Global Urban System: Networks and Hierarchies -- Towards Networked Systems -- Expansion and Concentration -- Leading Currencies in International Transactions -- The International Property Marke t-- Conclusion -- PART THREE: THE SOCIAL ORDER OF THE GLOBAL CITY -- Eight Employment and Earnings -- Three Cities, One Tale? -- Earnings -- Conclusion -- Nine Economic Restructuring as Class and Spatial Polarization -- Overall Effects of Leading Industries -- Social Geography -- Consumption -- Casual and Informal Labor Markets -- Race and Nationality in the Labor Marke t-- IN CONCLUSION -- Ten A New Urban Regime? -- Epilogue -- The Global City Model -- The Financial Order -- The Producer Services -- Social and spatial polarization.
Reissue of the edition published in 1991.
Includes bibliographical references and index.
Keywords: Financial services industry -- New York (State) -- New York; Financial services industry -- Japan -- Tokyo; Financial services industry -- England -- London; International finance; International economic relations; New York (N.Y.) -- Economic conditions; Tokyo (Japan) -- Economic conditions; London (England) -- Economic conditions